Neonatal management of orphaned puppies in shelters (Research, Society and Development, 2025)
The neonatal period is marked by significant physiological immaturity, especially neurological, making puppies totally dependent on maternal care and vulnerable to early mortality. Orphaned puppies, commonly rescued from shelters, have a higher risk of survival due to a lack of proper management. This study aimed to identify the main challenges in the neonatal management of orphaned puppies in shelters and to propose strategies to increase their survival and well-being. The methodology involved a literature review, application of questionnaires to volunteers at the Vira Lata Vira Amor Shelter, and analysis of rescue data from 2024. A total of 189 puppies were rescued—66 dogs (35%) and 123 cats (65%)—with 36 deaths (19%), 28 cats (78%) and 8 dogs (22%). Among the main difficulties reported were the scarcity of manpower, resources, and technical knowledge. It is concluded that standardized protocols and specific training are essential to improve the performance of shelters and reduce neonatal mortality.